Are k13 and plasmepsin II genes, involved in Plasmodium falciparum resistance to artemisinin derivatives and piperaquine in Southeast Asia, reliable to monitor resistance surveillance in Africa? - Francis Foguim Tsombeng (Malaria Journal, 2019)
Abstract Mutations in the propeller domain of Plasmodium falciparum kelch 13 (Pfk13) gene are associated with artemisinin resistance in Southeast Asia. Artemisinin resistance is defined by increased ring survival rate and delayed parasite clearance half-life in patients. Additionally, an amplification of the Plasmodium falciparum plasmepsin II gene (pfpm2), encoding a protease involved in hemoglobin degradation, has been found to be associated with reduced in vitro susceptibility to piperaquine in Cambodian P. falciparum parasites and with dihydroartemisinin–piperaquine failures in Cambodia. The World Health Organization (WHO) has recommended the use of these two genes to track the emergence and the spread of the resistance to dihydroartemisinin–piperaquine in malaria endemic areas. Although the resistance to dihydroartemisinin–piperaquine has not yet emerged in Africa, few reports on clinical failures suggest that k13 and pfpm2 would not be the only genes involved in artemisinin and piperaquine resistance. It is imperative to identify molecular markers or drug resistance genes that associate with artemisinin and piperaquine in Africa. K13 polymorphisms and Pfpm2 copy number variation analysis may not be sufficient for monitoring the emergence of dihydroartemisinin–piperaquine resistance in Africa. But, these markers should not be ruled out for tracking the emergence of resistance.